2021
DOI: 10.1177/1753495x211038157
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of SARS-CoV-2: A systematic review

Abstract: In this study, we discuss vertical transmission of SARS-CoV-2, and assess various maternal and neonatal outcomes based on the current evidence available. This systematic review using PRISMA guidelines revealed a total of 47 eligible studies describing 1188 SARS-CoV-2 positive pregnant women and 985 neonates for review. Utilizing the ‘Shah’s Classification System for Maternal-Fetal-Neonatal SARS-CoV-2 Intrauterine Infections’ by Shah et al., we found vertical transmission confirmed in 0.3% ( n = 3), probable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
(53 reference statements)
0
21
0
1
Order By: Relevance
“…There is evidence that infection with COVID-19 can occur in any way. In utero transmission is favored by the presence of angiotensin-converting enzyme receptors located at the level of the placenta [ 5 ]. In the intrapartum period, the fetus could be exposed to the virus located in vaginal fluids, as well as in maternal feces (during vaginal birth) [ 25 ] or the peritoneal fluids (during the cesarian section) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that infection with COVID-19 can occur in any way. In utero transmission is favored by the presence of angiotensin-converting enzyme receptors located at the level of the placenta [ 5 ]. In the intrapartum period, the fetus could be exposed to the virus located in vaginal fluids, as well as in maternal feces (during vaginal birth) [ 25 ] or the peritoneal fluids (during the cesarian section) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different comorbidities can influence vertical transmission [ 5 , 39 ]. For example, thrombophilia is a condition of hypercoagulability [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis including data up to 3 August 2021 and including over 14,000 babies born to mothers with SARS-CoV-2 infection found about 2% of babies tested positive with 14 confirmed mother-to-child vertical transmission, seven of which occurred in utero (Allotey et al, 2022). A slightly smaller systematic review of 47 studies and over 900 neonates reported that slightly less than 1% had a confirmed or probable vertical transmission of infection (Jeganathan and Paul, 2022). Similarly, a recent "systemic review of systematic reviews" suggested that mother to child transmission was relatively rare with 10.3389/fnins.…”
Section: Introductionmentioning
confidence: 99%
“… 1 A recent systematic review including a total of 47 studies describing 1188 SARS‐CoV‐2 positive pregnant women and 985 neonates reported the rate of neonatal infection to be as low as 0.3%. 2 …”
Section: Introductionmentioning
confidence: 99%